Students’ Perceptions toward the Teaching Strategy Used in Grammar Class - Edy Supriyanto (Jurnal Pendidikan Bahasa, 2022)
The present study aimed to capture the students' perceptions of their teachers' strategy in teaching grammar to children's classes. The research method conducted in the study was mixed methods. The number of participants was seven students studying at a junior level. The instruments used in the study were interviews and observation.The findings indicated that the students tended to perceive that the grammar lesson was a severe lesson for them. Hence, they preferred a more exciting and less complicated learning process. In sum, the students perceive that learning grammar should be done in a less severe matter but still encourages the students to learn effectively.